CYTOMORPHOMETRIC ANALYSIS OF BUCCAL CELLS IN BUILDING WORKERS EXPOSED TO POLYCYCLIC AROMATIC HYDROCARBON IN AND AROUND COIMBATORE DISTRICT - Singaravelu, Saranya Ramalingam; Srinivasan, Sushmitha; Dinesh, Deepak (International Journal of Current Pharmaceutical Research, 2017)
Objective: Building workers are exposed to a mixture of chemicals and polycyclic aromatic hydrocarbons at the time exposure by inhalation which is suspected to cause genetic damage. The aim of the study was to assess the level of genetic damage in south Indian building workers are exposed to PAHs. Methods: 30 Building workers and standardized control groups are examined for frequencies of micronuclei in buccal epithelial cells. Results: The genetic damage observed in the buccal cells of building workers was significantly higher than in controls. Chewing also related to genetic damage since the observed in PAHs exposed groups with chewers was significantly higher than non-chewing workers. Conclusion: Occupational exposure of PAHs from building workplaces has been associated with increased genetic damage and chewers represent an additional risk factor. Exposure to PAHs may be related to increased risk of cancer in building workers.